PENGARUH FLUSHING NACL 0,9% TERHADAP KEJADIAN FLEBITIS PADA PASIEN YANG TERPASANG KATETER INTRAVENA PERIFER - Aminah, Siti (STIKes Medistra Indonesia, 2020)
Background: Phlebitis incidents become indicator of hospital minimum service quality with standard occurrence <1.5%. If the phlebitis incidents are not managed as soon as possible, it is able to make complication and primary blood stream infectious seriously and fatal which causes the sepsis or death. The incidents can be managed by implementing nursing intervention standard operation procedure well such as one of the procedure by flushing NaCL 0,9%. Purpose: The aims of the research is to identify the flushing effect of NaCL, 0,9% against phlebitis incidents on clients applying perifer intravenous catheter. Method: research method used queasy experimental with non randomize control group pretest posttest design. This research done was at Zam-zam ward in RSUD Al IHSAN West Java Bandung Regency. Research samples were as many as 46 respondents who applied perifer intravenous catheter that divided became two groups of 23 respondents who were in intervention group and 23 respondents in control group. Phlebitis scale used PPI surveillance forms. Result: Test result of Man Whitney was obtained p value = 0,001 < α (0,05) that showed there was the difference phlebitis incident in each of intervention and control groups. Conclusion: There was the effect of NaCL 0,9% flushing against the phlebitis, consequently it is advisable to establish standard operating procedures flushing in the effort to prevent the occurrence of phlebitis.